Risk and protective factors influencing multiple sexual partners among adolescents in Rivers State - Vivian Ifeoma Ogbonna; Foluke Adeniji; Zubairu Iliyasu (Nigerian Journal of Medicine, 2023)
Introduction: The period of adolescence is characterised by changes and experimentations such as early sexual debut and multiple sexual partners (MSP). That might create issues with sexual and reproductive health that persist throughout one's life such as sexually transmitted infections plus HIV, unsafe abortion, and death. To inform contextualised and culturally appropriate preventive strategies, this study identified the forecasters of MSP among pubescents/adolescents in Rivers State. Materials and Methods: Using a cross-sectional research design, and multistaged sampling technique, 671 adolescents were interviewed with structured interviewer-administered questionnaires. Data were analysed using IBM SPSS version 26. Chi-square test analysis was performed to test for association in proportions between explanatory (sociodemographic variables, factors at the individual, peer, family, community, and national domains) and outcome (MSP) variables. The proportion of sexually experienced respondents with MSP was determined and adjusted odd ratios of predictors derived from multivariate logistic regression models. Results: Out of the 671 adolescents (10–19 years) surveyed, 53.1% were female, and 29 (4.3%) are married. The median age and the interquartile range were 18.0 years. Nearly half 313 (46.6%) of the respondents were sexually experienced, of which 148 (47.3%) had MSP. After adjusting for covariates, religion, sex, employment, father's education, individual perceptions, peer, family, and community norms predicted MSP (P < 0.05). Specifically, respondents with religious affiliations were less likely (adjusted odds ratio [aOR] =0.43, 95% confidence interval [CI]: 0.22–0.87, P = 0.019) than nonreligious/catholic respondents to have several sexual partners. Similarly, female adolescents were less likely to have MSP (aOR = 0.57, 95% CI: 0.33–0.98, P = 0.042). Relative to those whose fathers have no formal education, respondents whose fathers have secondary (crude odds ratio = 0.48, 95% CI: 0.26–0.83, P = 0.001) and tertiary education have lower odds of having MSP. Respondents with higher individual, peer, and community domain scores had at least a threefold raised likelihood of having MSP. Conclusion: A large proportion of sexually experienced adolescents have MSP; religious affiliations were shown to be protective and should be encouraged. Employed adolescents and males are more at risk. Gender-appropriate reproductive health actions for adolescents need to be contextualised at different levels.